Literatura premiada entra na escola?: a presença dos livros premiados pela FNLIJ, na categoria criança, em bibliotecas escolares da Rede Municipal de Belo Horizonte - Cristiane Dias Martins da Costa (2009)
The present research was done within the field of Education and Language, and is aimed at investigating literary production for children. The corpus of this research is made up of 49 book titles awarded by Brazils National Foundation for Children's and Young People's Books (FNLIJ), category children, from the years 1974 to 2006. The winner of the prize awarded by FNLIJ, chosen by dozens of voters, was used in this study due to its high relevance for publications aimed at children in Brazil. The research was guided by the principles of the main theoreticians of education and reading practices. The basic bibliography was mostly taken from Coleção Literatura e Educação (Literature and Education Collection, coordinated by GPELL - Research Group on Literary Literacy) as well as from studies and researches developed by this group. The production of some authors like Bourdieu, Chartier, Coelho, Lajolo, Soares and Zilberman, among others, is also to be taken into account. This research was grounded in two main analysis procedures: tracing the presence of awarded books for children in the public schools libraries of Belo Horizonte through the use of a form given to the professionals responsible for the libraries, and analyzing these books according to the evaluation criteria of the School Library National Program (PNBE). This tracing made by the municipal school system of Belo Horizonte (RMBH) has revealed that the professionals working on school libraries do not effectively make use of the work made by FNLIJ, that is, only 3 of the 41% interviewed professionals, who have said they knew about FNLIJ, use the awarding criteria when purchasing book titles for the school library. Nevertheless, the quality of the awarded books is unquestionable, which can be proven to be true as they were analyzed in accordance with the criteria set out by PNBE/2008: Textual and thematic quality as well as quality of the graphic project. Finally, it was concluded that there is a big disparity concerning the presence of books from one school to another. In certain schools, there are 30 of the 49 researched books, while in others there is only one of these books. The proposal of analyzing the presence of literary production awarded by FNLIJ, in the category children, is to contribute with the studies that focus on different aspects of Brazilian literature for children.